Managing in a service-focused world : I, team, stewards and marketplace - Williams, Roger K. (IT Governance Publishing, 2014)
In this book, Roger K. Williams adapts tried and trusted principles of IT service management (ITSM) into a framework for personal and professional development. He treats management as a service, presenting the idea that the effectiveness of a manager is best judged by the views of the key stakeholders: the manager themselves, their team, their leaders and their customers. The book takes its examples from IT service management, but the clear and direct style means that managers in any industry can understand and implement the ideas. It helps readers: create a personal development plan to improve management skills; increase their professional standing; understand how to work with a team to keep them engaged and working effectively; and work better with customers and external stakeholders, resulting in better, mutually beneficial relationships. --